MODEL INKUIRI TERPIMPIN BERPASANGAN DALAM PEMBELAJARAN MENULIS KREATIF KONSERVASI BUDAYA BERBASIS PEMBENTUKAN KARAKTER PESERTA DIDIK - Zulaeha, Ida (Jurnal Penelitian Pendidikan, 2013)
Learning to write the creative of reports needs planning to explore and involve the studentsâ ability. The activity of finding, observing and arranging confidently are the common activities in building the studentsâ character. Model of guided inquiry in pairs is used in learning to write the creative of reports. This research aims to know whether this model is effective used to guide the students being competent to write the creative of reports laden cultural conservation in character building. In this research used the randomized posttest only group design. The research conducted on studentsâ Junior High School. The result showed that the students were more competent in writing the creative of reports at the model of guided inquiry in class pairs categorized well and thoroughly with the mean of 82,32 than the control class of investigation group with the mean of 79,23. The characters accustomed was showed in the creative writing of reports by students the model of guided inquiry in pairs are more complete, including environment care, social care, creative, discipline, and patriotic.